Palm oil based polyurethane/clay nano composite. - Mustapha, Saari; Rihayat, Teuku; Mahmood, Mohd Hilmi (2011)

(untitled)
A method for producing a nanocomposite comprising modifying montmorillonite with a cationic surfactant to obtain an organoclay and combining the organoclay with a palm oil-based polyurethane (PU) elastomer.